Fabrication of hierarchical Sn-doped ZnO nanorod arrays through sonicated sol−gel immersion for room temperature, resistive-type humidity sensor applications. Issue 8 (June 2016) - Ismail, A.S.; Mamat, M.H.; Md. Sin, N.D.; Malek, M.F.; Zoolfakar, A.S.; Suriani, A.B.; Mohamed, A.; Ahmad, M.K.; Rusop, M.
Abstract: Hierarchical tin (Sn)-doped zinc-oxide (ZnO) nanorod arrays (SZO) were deposited onto Al-doped ZnO-coated glass substrate by using a sonicated sol–gel immersion method for resistive-type humidity sensor applications. X-ray diffraction patterns revealed that the deposited SZO arrays exhibit a wurtzite structure. SZO possessed smaller average diameter, crystallite size, and thickness than the undoped sample did. The SZO film also exhibited compressive strain and tensile stress values of −0.033% and 77 MPa, respectively. Our result showed the sensitivity of the SZO based-sensor improved compared with that of the undoped ZnO, with values of 3.41 and 1.41 at 40% to 70% RH and 70% to 90% RH, respectively. The response and recovery times of the SZO based humidity sensor improved to 230 and 30 s, respectively. All these results indicated that SZO had high potential for humidity-sensor applications.